A Comprehensive and Person-Centered View of the Association Between the Dark Triad and Youth Mental Health - Hu, Yunjun; Lan, Xiaoyu (Frontiers in Psychiatry, 2022)
Using a dual person-centered approach, the current study examined the Dark Triad profiles and mental health profiles among a large-scale sample of high school students. The study also simultaneously examined whether the emerging Dark Triad profiles could diverge in mental health profiles, delineating a thorough, and person-centered view of this association. To achieve these research aims, 1,640 Chinese high school students (Mage = 16.78; SD = 0.68; 57.6% females) participated in this study, and they were uniformly instructed to complete a set of well-established questionnaires. Results from latent profile analyses revealed five Dark Triad profiles—low Machiavellianism-psychopathy (7.4%), benevolent (61.7%), highly malevolent (6.7%), low narcissism (8.8%), and malevolent (15.4%)—and the following four mental health profiles: flourishing (37.7%), vulnerable (16.4%), troubled (33.9%), and highly troubled (12.4%). Moreover, results from multiple multinomial regression analyses showed that, among all five empirically derived Dark Triad profiles, students with the low Machiavellianism-psychopathy profile exhibited the highest probability of being “flourishing,” whereas those with the low narcissism profile showed the highest likelihood of being “highly troubled.”